2008
DOI: 10.1103/physrevb.78.020406
|View full text |Cite
|
Sign up to set email alerts
|

Chemical potential landscape in band filling and bandwidth-control of manganites: Photoemission spectroscopy measurements

Abstract: We have studied the effects of band filling and bandwidth control on the chemical potential in perovskite manganites R1−xAxMnO3 (R : rare earth, A : alkaline earth) by measurements of corelevel photoemission spectra. A suppression of the doping-dependent chemical potential shift was observed in and around the CE-type charge-ordered composition range, indicating that there is charge self-organization such as stripe formation or its fluctuations. As a function of bandwidth, we observed a downward chemical potent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
6
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The band dispersions obtained by ARPES were almost the same as those of LSMO thin films. These results are almost the same as the previous results of bulk samples 8,14 and surely demonstrate that the electronic structure of the NSMO thin films on STO substrates was almost the same as the bulk samples due to the effects of relaxation. The reduction in the ferromagnetic transition temperature compared to LSMO cannot be ascribed to the decrease in the bandwidth but to the decrease in the coherent spectral weight of the e g band.…”
supporting
confidence: 92%
See 4 more Smart Citations
“…The band dispersions obtained by ARPES were almost the same as those of LSMO thin films. These results are almost the same as the previous results of bulk samples 8,14 and surely demonstrate that the electronic structure of the NSMO thin films on STO substrates was almost the same as the bulk samples due to the effects of relaxation. The reduction in the ferromagnetic transition temperature compared to LSMO cannot be ascribed to the decrease in the bandwidth but to the decrease in the coherent spectral weight of the e g band.…”
supporting
confidence: 92%
“…From core-level photoemission studies, we found that the behavior of the chemical-potential shift was not much different from that of the bulk NSMO samples. 8 The band dispersions obtained by angle-resolved photoemission spectroscopy ͑ARPES͒ were almost the same as those of LSMO thin films. 9 These results show that the electronic structure of the NSMO thin films were similar to those of the bulk samples due to the effects of relaxation.…”
mentioning
confidence: 76%
See 3 more Smart Citations